The Effect of Political Connections, Leverage, Audit Committee Gender, and Company Size on Audit Delay - Hilda Salman Said; Sultan Muhammad Dhava; Ruri Octari Dinata (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Audit delay is the number of days needed by the auditor to complete the audit work, measured from the end of the financial year until the issuance of the audited financial report. Timeliness means having information available to make decisions before it loses its capacity to influence decisions. This study aims to determine the effect of political connections, leverage, audit committee gender, and company size on audit delay in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021, both simultaneously and partially. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. This study uses secondary data in the form of annual financial reports from the property and real estate sector listed on the Indonesia Stock Exchange (IDX). ) in 2017 to 2021. With a company population of 10 companies with an observation period of five years and obtained a sample data of 50 observational data. This research is quantitative. The data collection technique used purposive sampling with the logistic regression research method which was processed using SPSS software. The results of the tests that have been carried out indicate that simultaneously the variables of political connections, leverage, audit committee gender, and company size have a significant effect on audit delay. Partially, political connections, leverage, and audit committee gender have no significant effect on audit delay. Meanwhile, company size has a significant effect on audit delay.